Isolation of the Pathogen Rickettsia sp. Strain Atlantic Rainforest From Its Presumed Tick Vector, Amblyomma ovale (Acari: Ixodidae), From Two Areas of Brazil. Issue 4 (4th May 2016) - Nieri-Bastos, Fernanda A.; Horta, Maurício C.; Barros-Battesti, Darci Moraes; Moraes-Filho, Jonas; Ramirez, Diego G.; Martins, Thiago F.; Labruna, Marcelo B.
Abstract: In this study, Amblyomma ovale Koch ticks were collected from domestic dogs in two localities of the Atlantic rainforest biome of Brazil: 1) the Paty Valley of the Chapada Diamantina National Park, Bahia state (northeastern Brazil), and 2) Adrianópolis, Paraná state (southern Brazil). Ticks were screened for the presence of Rickettsia- like structures by the hemolymph test with Giménez staining, and then processed for isolation of rickettsiae in Vero cell culture by the shell-vial technique. Rickettsiae were isolated from one A. ovale tick of each of the two localities. The two isolates were successfully established in the laboratory with several passages, each one reaching >90% infection of the cells. The two isolates were identified as the spotted fever group (SFG) agent Rickettsia sp. strain Atlantic rainforest, as their gltA (350 bp), ompB (781 bp), and ompA (567 bp) gene fragments were 100% equal to GenBank corresponding sequences of the original strain Atlantic rainforest, reported to be infecting a human in southeastern Brazil, and also 100% equal to the available ompA sequence of strain Bahia, reported to be infecting a human in Paty Valley, the same area of the present study in Bahia state. Ten dogs from Paty Valley were serologically tested against rickettsial antigens by the indirect immunofluorescence antibody test. At least 60% of them were seroreactive to SFG rickettsiae . The role of A. ovale as vector of Rickettsia sp. strain Atlantic rainforest in the Paty Valley area, as well as in other parts of Latin America, is discussed.